The current comparator - Moore, W. J. M.; Miljanic, P. N. (London P. Peregrinus on behalf of the Institution of Electrical Engineers, 1988)
This book presents the basic theory of the current comparator, methods of construction leading to high ratio accuracies and the operating principles of the various applications.
Electronic reproduction.
Keywords: Electronic transformers; Electric transformers; Electronic books